2011
DOI: 10.4028/www.scientific.net/amr.194-196.1126
|View full text |Cite
|
Sign up to set email alerts
|

Researches and Application of Railway Wind-Break Wall

Abstract: Railway wind-break wall is widely used, which is of significant importance to prevent running vehicles from suffering the risk of overturning. In the paper, application of railway wind-break wall and specific details of its structure are introduced. Wind tunnel test and CFD simulation are widely used in the researches on the performance of railway wind-break wall and some important results are summarized. Based on the review, developments of railway wind-break wall in the future are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The reduction in hardness observed across all groups following storage is likely attributed to enzymatic protein degradation, as documented in prior studies [15,43,44]. Our study showed that lower stocking densities of 35 and 50 kg•m −3 produced firmer fillets compared to the higher density of 65 kg•m −3 , suggesting that fish welfare during rearing impacts the ultimate quality of fillets [15].…”
Section: Discussionsupporting
confidence: 81%
“…The reduction in hardness observed across all groups following storage is likely attributed to enzymatic protein degradation, as documented in prior studies [15,43,44]. Our study showed that lower stocking densities of 35 and 50 kg•m −3 produced firmer fillets compared to the higher density of 65 kg•m −3 , suggesting that fish welfare during rearing impacts the ultimate quality of fillets [15].…”
Section: Discussionsupporting
confidence: 81%
“…Li et al 7 conducted research on the application of windbreaks for railways that are widely and progressively in use and reported about the role of such walls in preventing rollovers of trains. Zhou et al, 8 while studying windbreaks, had concluded that the train pantographs perform better in the presence of windbreaks.…”
Section: Introductionmentioning
confidence: 99%